Pengaruh Supervisi Akademik Kepala Sekolah dan Budaya Sekolah terhadap Mutu Mengajar Guru - Setio Handhini, Lidya; Ahmad, Syarwani; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2020)
The objectives of this study were 1) to analyze the effect of the principal's academic supervision on the teaching quality; 2) to analyze the influence of school culture on the teaching quality; 3) to analyze jointly academic supervision of the principal and school culture on the teaching quality. The samples of this study were 47 PNS teachers and 10 non-PNS teachers. Data collection techniques were 1) questionnaire; 2) documentation. The data analysis technique uses the SPSS Version 21 software program application. The results showed that 1) there is significant effect of the principal's academic supervision on the teaching quality; 2) there is a significant effect of school culture on the quality of teaching; 3) there is a significant effect of principal academic supervision and school culture together on the teaching quality of teachers at SMP Negeri 1 Prabumulih.